THE EFFECT OF STRESS RELAXATION ON WHISKER GROWTH ESTIMATION - QIANG Lei; HUANG ZaiXing; XIAO Ye; GAO Jun (Jixie qiangdu)
To describe the phenomenon of the stress generation and stress relaxation occurring simultaneously in the process of whisker growth,a UMAT subroutine in Abaqus is developed to solve the elasto-plastic creep constitutive model by means of the return-mapping algorithm.The finite element simulations show that,compared with the elasto-plastic model in Abaqus,the elasto-plastic creep constitutive model characterizes the stress relaxation of material better.Using this subroutine,we calculate the change of stress in a specimen of Pb-free solder.In terms of the change of stress,the whisker growth rate is evaluated.And the effect of the grain size on the whisker growth rate is discussed.